Effect of electron irradiation on the crystallite size, grain size and band gap energy of electrodeposited cadmium sulfide thin films. (2021) - Gangawane, S.A.; Malekar, V.P.; Fulari, V.J.
Abstract: Here, cadmium sulfide (CdS) thin films have been prepared by electrodeposition method using aqueous basic electrolyte. The electrodeposition of CdS thin films has been carried out by varying the concentrations. The deposition potential of the compound was studied by cyclic voltammetry. The as-deposited and irradiated CdS thin films were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), and optical absorption technique for different bath concentration. The XRD shows multi crystalline phases having (1 1 0) major peak. The band gap was found to be 2.3 and 2.4 eV was as deposited and irradiated flim. The layers were subjected to irradiation with 6 MeV electrons.